Randomized Trial of FOLFOX 4 and FOLFIRI in The Treatment of Advance Colorectal Cancer : Randomized Trial of FOLFOX 4 and FOLFIRI - Kumari, Reeta; Haider, Ghulam; Aalam, Nargis; Shah, Aamera; Sarim, Tooba; Abid, Khadijah (Pakistan Journal of Health Sciences, 2023)
Colorectal cancer is a major global health concern, ranking third in prevalence and second in mortality. Developed countries have high incidence rates, while Pakistan is considered a low-risk region. Metastatic colorectal cancer requires targeted therapies like FOLFIRI and FOLFOX4, but their effectiveness in Pakistan is unknown. This study aims to provide insights, guide treatment decisions, and expand global understanding in the field. Objective: To compare therapeutic effects of FOLFOX4 and FOLFIRI for advanced colorectal cancer patients. Methods: The Medical Oncology Department of Jinnah Postgraduate and Medical Centre conducted a randomized controlled trial research from May 2022 to February 2023. Hundred patients of advanced colorectal cancer with a confirmed diagnosis of age 18 to 80 years, of either gender, were included. Randomly, 50 of these patients were in FOLFIRI group, and 50 in FOLFOX4 group. Both groups were compared for the treatment outcomes. Results: In the FOLFIRI group, the total response rate was 66%, whereas in the FOLFOX 4 group, it was 78%. In the FOLFIRI group, the median time to progression was 8 months, but in the FOLFOX 4 group, it was 9 months (p=0.06). In the FOLFIRI group, the total median survival time was 13 months, whereas in the FOLFOX 4 group, it was 14 months (p=0.280). Conclusions: The response rates between the two groups were similar, while FOLFOX 4 had a little higher rate of tumor control. FOLFIRI had a lower incidence of neutropenia, whereas FOLFOX 4 had a lower incidence of nausea and vomiting.